Data from: Can novel pest outbreaks drive ecosystem transitions in northern-boreal birch forest? - Vindstad, Ole Petter Laksforsmo; Jepsen, Jane Uhd; Ek, Malin; Pepi, Adam; Ims, Rolf Anker (Zenodo, 2019)
1. The boreal biome exhibits distinct alternative ecosystem states with high and low levels of tree-cover. Insect outbreaks facilitated by climate warming could potentially drive transitions from high to low tree-cover states. We investigated whether two key premises for such outbreak-induced transitions – critical thresholds (tipping points) and positive feedbacks that could maintain alternative states – are present in the northern-boreal mountain birch forest of Fennoscandia. Here, climate warming has promoted range expansions of defoliating geometrid moths, resulting in novel, severe multispecies outbreaks, most recently during 2002-2010. 2. We conducted regional-scale field surveys of forest damage and recovery in 280 mountain birch stands in a northeast Norway immediately after the outbreak (2010) and six years later (2016). Satellite-derived time series of the normalized difference vegetation index (NDVI) provided an index of stand defoliation during the outbreak period. 3. The proportion of dead stems per stand displayed a bimodal distribution, with stands generally being either lightly or severely damaged. This was due to a critical threshold in the relationship between defoliation and stem mortality, with mortality rates increasing abruptly in stands experiencing a mean drop in NDVI of more than 4 % during the outbreak. The two key forest regenerative pathways – basal sprouting and sapling production – both displayed positive feedbacks with surviving stems and trees, so that regeneration success declined with increasing damage to the mature tree layer. These feedbacks imply that stands which have been forced across critical defoliation thresholds and suffered collapses of living tree cover may struggle to recover, especially if the loss of positive regenerative feedbacks is compounded by ungulate browsing on birch recruits. 4. Synthesis. The north Fennoscandian mountain birch forest displays critical thresholds and positive feedbacks that conform to theoretical expectations for a system that could be ...